2015
DOI: 10.1039/c4fo01067a
|View full text |Cite
|
Sign up to set email alerts
|

Combined heterogeneous distribution of salt and aroma in food enhances salt perception

Abstract: Aroma-taste interactions and heterogeneous spatial distribution of tastants were used as strategies for taste enhancement. This study investigated the combination of these two strategies through the effect of heterogeneous salt and aroma distribution on saltiness enhancement and consumer liking for hot snacks. Four-layered cream-based products were designed with the same total amount of sodium and ham aroma but varied in their spatial distribution. Unflavoured products containing the same amount of salt and 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…There, we concluded that the perception of saltiness could be controlled by combining different food components varying in their flavour content. Such a conclusion is consistent with the results of previous studies on the inhomogeneous distribution of tastants or aroma compounds (Emorine et al, 2015;Mosca et al, 2010;Nakao et al, 2013). For instance, in layered cream-based snack foods that varied in salt distribution, Emorine and coworkers (2013) demonstrated that salt perception was mostly dependent on the salt concentration in the saltier layer.…”
Section: The Link Between Flavour and Heterogeneitysupporting
confidence: 91%
See 3 more Smart Citations
“…There, we concluded that the perception of saltiness could be controlled by combining different food components varying in their flavour content. Such a conclusion is consistent with the results of previous studies on the inhomogeneous distribution of tastants or aroma compounds (Emorine et al, 2015;Mosca et al, 2010;Nakao et al, 2013). For instance, in layered cream-based snack foods that varied in salt distribution, Emorine and coworkers (2013) demonstrated that salt perception was mostly dependent on the salt concentration in the saltier layer.…”
Section: The Link Between Flavour and Heterogeneitysupporting
confidence: 91%
“…Lévy et al (2006) suggested that consumer exposure to foods with multiple types of stimuli should lead to an increase in longterm liking. It was proposed that variations in texture and tastants can be used to provide a discontinuous stimulation and thus reduce adaptation of specific sensory perceptions (Emorine et al, 2014(Emorine et al, , 2015Funami et al, 2016;Mosca et al, 2010Mosca et al, , 2012.…”
Section: Rationale and Thesis Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…Similar conclusions were obtained in studies of cream-based multi-layer savory pastries. Heterogeneous distribution of salt resulted in products with comparable sensory perceptions while containing 25% less sodium in formulation [ 65 ]. A similar study also showed up to a 42% reduction in sodium content of cereal- and cream-based multi-layer products by heterogeneous distribution of salt in the products [ 66 ].…”
Section: Adoptable Interventions For Reducing the Sodium In Procesmentioning
confidence: 99%